2019
DOI: 10.1371/journal.pone.0210357
|View full text |Cite
|
Sign up to set email alerts
|

Environmental DNA metabarcoding for fish community analysis in backwater lakes: A comparison of capture methods

Abstract: The use of environmental DNA (eDNA) methods for community analysis has recently been developed. High-throughput parallel DNA sequencing (HTS), called eDNA metabarcoding, has been increasingly used in eDNA studies to examine multiple species. However, eDNA metabarcoding methodology requires validation based on traditional methods in all natural ecosystems before a reliable method can be established. To date, relatively few studies have performed eDNA metabarcoding of fishes in aquatic environments where fish co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
133
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(140 citation statements)
references
References 49 publications
5
133
2
Order By: Relevance
“…Most of the studies which targeted specific species employed real-time PCR platforms and emphasized the high detection sensitivity of eDNA assays (Biggs et al, 2015;Dougherty et al, 2016;Ikeda, Doi, Tanaka, Kawai, & Negishi, 2016;Takahara, Minamoto, & Doi, 2013). However, some studies reported significant inhibitory effects on PCR amplification (Doi, Kanato, et al, 2017b;Fujii et al, 2019;Jane et al, 2015;Sigsgaard, Carl, Møller, & Thomsen, 2015), leading to false-negative results. Such inhibitory effects can also induce uncertain quantification of eDNA concentration (McKee, Spear, & Pierson, 2015), which would hinder attempts to estimate the abundance and biomass of target organisms based on the amount of DNA (Baldigo, Sporn, George, & Ball, 2017;Doi, Inui, et al, 2017a;Lacoursière-Roussel, Rosabal, & Bernatchez, 2016;Yamamoto et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies which targeted specific species employed real-time PCR platforms and emphasized the high detection sensitivity of eDNA assays (Biggs et al, 2015;Dougherty et al, 2016;Ikeda, Doi, Tanaka, Kawai, & Negishi, 2016;Takahara, Minamoto, & Doi, 2013). However, some studies reported significant inhibitory effects on PCR amplification (Doi, Kanato, et al, 2017b;Fujii et al, 2019;Jane et al, 2015;Sigsgaard, Carl, Møller, & Thomsen, 2015), leading to false-negative results. Such inhibitory effects can also induce uncertain quantification of eDNA concentration (McKee, Spear, & Pierson, 2015), which would hinder attempts to estimate the abundance and biomass of target organisms based on the amount of DNA (Baldigo, Sporn, George, & Ball, 2017;Doi, Inui, et al, 2017a;Lacoursière-Roussel, Rosabal, & Bernatchez, 2016;Yamamoto et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We suspect that these differences are probably attributable to the size-abundance distribution of fish communities, which indicates that species with smaller body sizes are more abundant in lakes than are those of larger body size 34 . Lakes, particularly those characterized by brackish waters, harbor numerous marine-migratory fish species that show tolerance to saltwater, and eDNA metabarcoding surveys of lakes have detected many such migratory species 16,27 . Given that the timing of occurrence of species influences the detection of their eDNA 35 , the timing of migration would influence the detection of migratory species in lakes using eDNA metabarcoding, and consequently, may contribute to the infrequent detection of saltwater-tolerant species by eDNA metabarcoding in eDNA sampling surveys.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in molecular ecology have seen the emergence of environmental DNA (eDNA) analysis as a useful approach for investigating the distribution and richness of aquatic and terrestrial organisms [10][11][12][13][14][15][16] , and high-throughput parallel DNA sequencing has recently been applied to eDNA methods for simultaneous detection of multiple taxa, known as eDNA metabarcoding [16][17][18][19][20][21] . For example, Miya et al 22 designed and applied universal PCR primers (MiFish primers) for fish eDNA metabarcoding, and MiFish primers recently developed for different fish taxa 15,16,23 have shown higher performance compared with other primers types 24 and PCR conditions 25 . eDNA metabarcoding is acknowledged to be an exceptionally useful and powerful tool for community surveys [16][17][18][19][20]26,27 , and consequently, in recent years, this technique has been widely applied in aquatic community surveys worldwide 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Even if fish biomass could be reportedly determined by eDNA [36], eDNA has been limited to certain species. Moreover, it has not been applied to metabarcoding because of species-specific amplification rates [37], environment-dependent degradation rates [18, 38], and PCR inhibition by environmental factors [12, 14]. Therefore, the estimate of biomass requires a complex model and the possible use of eDNA for this purpose needs to be verified.…”
Section: Methodsmentioning
confidence: 99%
“…Although a number of studies on biodiversity have been reported [8, 9], most of them have focused on local areas of ecologic or economic importance to aquaculture [10], unique ecosystems (e.g., coral reefs, mangroves, tropical islands) [4, 6], and other services [11]. In contrast, biodiversity evaluations that include various regions at the same time have not been carried out, because traditional monitoring methods (observations and/or capture) require considerable financial and labor resources to cover a wide range of habitats [12, 13]. Also, particularly for rare and endangered species, monitoring using traditional methods can negatively affect the organisms and their habitat during the survey.…”
Section: Introductionmentioning
confidence: 99%